Large eddy simulations of methane emission from landfill and mathematical modeling in the far field - Boghi, Andrea; Harris, Neil R. P.; Waombo, Kennedy (MDPI, 2025)
Greenhouse gases such as methane will be generated from the landfilling of municipal waste. The emissions of noxious gas from landfills and other waste disposal areas can present a significant hazard to the environment and to the health of the population if not properly controlled. In order to have the harmful gas controlled and mitigate the environmental pollution, the extent to which the gas will be transported into the air at some time in the future must be estimated. The emission estimates (inventories) are combined with atmospheric observations and modeling techniques. In this work, large eddy simulation (LES) is used to determine the dispersion of methane in the atmosphere at large distances from the landfill. The methane is modeled as an active scalar, which diffuses from the landfill with a given mass flux. The Boussinesq approximation has been used to embed the effect of the buoyancy in the momentum equation. A logarithmic velocity profile has been used to model the wind velocity. The results in the far field show that the mean concentration and concentration rms of methane, appropriately scaled, are self-similar functions of a certain combination of the coordinates. Furthermore, the LES results are used to fit the parameters of the Gaussian plume model. This result can be used to optimize the placement of the atmospheric receptors and reduce their numbers in the far-field region, to improve emissions estimates and reduce the costs.
Keywords: 37 Earth Sciences; 3701 Atmospheric Sciences; 13 Climate Action; 3702 Climate change science; LES; self-similarity; methane; atmospheric receptors; landfill; emissions